Aktualisasi Konsep ‘Adalah Dalam Hukum Pernikahan Perspektif Fiqh Syafi’iyyah - Mazani Hanafiah (Institut Agama Islam Al-Aziziyah Samalanga, 2022)
The practice of marriage in society is sometimes constrained by fairness marriage guardians and marriage witnesses, even though not all sharia cases for their validity are fair and spiritual, and some are not a requirement at all. This study seeks to actualize the concept of 'is', and the clarity of fair status on guardians and witnesses of marriage. This study uses a type of qualitative research using a normative approach, data collection techniques through library research, data collected through primary and secondary sources were analyzed using descriptive analysis methods (content analysis). The author finds that 'is is a trait that is embedded in a person's soul so that he avoids committing major sins, does not continue to do small sins, obeys to dominate his disobedience, and maintains honor. The provisions of marriage guardians and marriage witnesses must be fair in the hajiy (secondary) category, so that their justice is enough to know their appearance, they do not have to know their inner fairness. Marriages that take place with special guardians and marriage witnesses who commit minor sins are still valid if their obedience dominates the immorality, it is fair for them to just look at their daily behavior that they maintain religion and honor, while marriages carried out by guardians are still valid even if they are wicked.